1990
DOI: 10.1126/science.2274789
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mechanisms of Tumor Suppression by the Human p53 Gene

Abstract: Mutations of the gene encoding p53, a 53-kilodalton cellular protein, are found frequently in human tumor cells, suggesting a crucial role for this gene in human oncogenesis. To model the stepwise mutation or loss of both p53 alleles during tumorigenesis, a human osteosarcoma cell line, Saos-2, was used that completely lacked endogenous p53. Single copies of exogenous p53 genes were then introduced by infecting cells with recombinant retroviruses containing either point-mutated or wild-type versions of the p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
224
1
12

Year Published

1996
1996
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(250 citation statements)
references
References 31 publications
13
224
1
12
Order By: Relevance
“…The wild-type form of protein acts as tumour suppressor, as for example the transfection of the wild-type gene into human osteosarcoma cells lacking endogenous p53 abrogates the neoplasticity of the cells (Chen et al, 1990). Furthermore p53 was shown to be lost or to contain mutations that inactivate p53 in about half of almost all human cancer types arising from a wide spectrum of tissues Caron de Fromentel and Soussi, 1992;Hollstein et al, 1994;Marshall, 1991;Nigro et al, 1989) and is now known to be the most commonly altered gene in human tumour (Caron de Fromentel and Soussi, 1992;Hollstein et al, 1994Hollstein et al, , 1996.…”
Section: From Oncogene To Tumour Suppressor Genementioning
confidence: 99%
“…The wild-type form of protein acts as tumour suppressor, as for example the transfection of the wild-type gene into human osteosarcoma cells lacking endogenous p53 abrogates the neoplasticity of the cells (Chen et al, 1990). Furthermore p53 was shown to be lost or to contain mutations that inactivate p53 in about half of almost all human cancer types arising from a wide spectrum of tissues Caron de Fromentel and Soussi, 1992;Hollstein et al, 1994;Marshall, 1991;Nigro et al, 1989) and is now known to be the most commonly altered gene in human tumour (Caron de Fromentel and Soussi, 1992;Hollstein et al, 1994Hollstein et al, , 1996.…”
Section: From Oncogene To Tumour Suppressor Genementioning
confidence: 99%
“…Previous reports have shown that some p53 mutants are capable of conferring increased tumorigenicity (Dittmer et al, 1993) and can induce a highly transformed phenotype as well as growth advantage in cell lines (Wolf et al, 1984;Chen et al, 1990). Since we did not detect abnormal forms of p53, association with hsc70 or recognition by monoclonal antibody PAb240 in ABS cells (data not shown), it is unlikely that a selection for p53 mutations has occurred during transformation by Ad5 E1 and E4orf6 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 gene encodes a nuclear phospho-protein which functions as a tumor suppressor by negative regulation of cell cycle progression and the induction of apoptosis (Finlay et al, 1989;Chen et al, 1990;Gottlieb and Oren, 1996;Ko and Prives, 1996;Levine, 1997). p53 is also involved in the regulation of cell di erentiation (Prokocimer and Rotter, 1994;Rotter et al, 1994).…”
Section: Introductionmentioning
confidence: 99%